Representation of molecular structures with persistent homology for machine learning applications in chemistry - Jacob Townsend (Nature Portfolio, 2020)
The choice of molecular representations can severely impact the performances of machine-learning methods. Here the authors demonstrate a persistence homology based molecular representation through an active-learning approach for predicting CO2/N2 interaction energies at the density functional theory (DFT) level.